Effects of rare earth oxide Y2O3 on microstructure and mechanical properties of proeutectoid ferrite/granular bainitic coating. Issue 12 (10th May 2016) - Xing, X.L.; Zhou, Y.F.; Zhuo, Y.G.; Wang, J.B.; Yang, Y.L.; Yang, Q.X.
Abstract: Abstract : The effects of rare earth oxide Y2 O3 additive on microstructure and mechanical properties of proeutectoid ferrite/granular bainitic coating by flux-cored arc welding were investigated. The results show that the primary austenite in the bainitic coating can be refined by Y2 O3 . The grain size of primary austenite is decreased from 51.2 µm to 40.1 µm with the increased Y2 O3 . The size of proeutectoid ferrite is decreased significantly and the fraction of the bainite is increased, which in turn facilitates the uniform distribution of the M/A island. Large number of the dislocation martensite is transformed into M/A. With the increased Y2 O3 additive, the hardness and the tensile strength of the coating increases from HV 272 ± 13 to HV 312 ± 8 and from 764 ± 10 MPa to 885 ± 12 MPa, respectively. Moreover, the wear resistance of the coating with Y2 O3 additive is increased simultaneously.